A Villa in Sicily: Vino and Death (A Cats and Dogs Cozy Mystery-Book 3) - Fiona, Grace (Lukeman Literary, 2021)
"Very entertaining. Highly recommended for the permanent library of any reader who appreciates a well-written mystery with twists and an intelligent plot. You will not be disappointed. Excellent way to spend a cold weekend!" --Books and Movie Reviews (regarding Murder in the Manor) A VILLA IN SICILY: VINO AND DEATH is book #3 in a charming new cozy mystery series by bestselling author Fiona Grace, author of Murder in the Manor, a #1 Bestseller with over 100 five-star reviews (and a free download)! Audrey Smart, 34, has made a major life change, walking away from her life as a vet (and from a string of failed romance) and moving to Sicily to buy a $1 home-and embark on a mandatory renovation she knows nothing about. Audrey is busy working to open the town's new shelter, while also renovating her own problematic home-and dating again. With the help of friends, she begins taking in sick strays. But not everyone in town is grateful for her services, and she soon makes unexpected enemies. Audrey's small Sicilian town hires a new building inspector to deal with the influx of $1 home owners-and he sets about making Audrey's idyllic Sicilian life utterly miserable. Just when things can't get any worse, the inspector turns up dead-leaving Audrey as the main suspect. Audrey, without an alibi, is under more pressure than she's ever been to solve the crime. But the inspectors list of enemies was long. Very, very long. Can she solve this impossible case? A laugh-out-loud cozy packed with mystery, intrigue, renovation, animals, food, wine-and of course, love-A VILLA IN SICILY will capture your heart and keep you glued to the very last page.
Keywords: Krimi, detektivky